Multidimensional Measurement of Richness: Theory and an Application to Germany - Andreas Peichl; Nico Pestel (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Closely following recent innovations in the literature on the multidimensional measurement of poverty, this paper provides similar measures for the top of the distribution using a dual cutoff method to identify individuals, who can be considered as rich in a multidimensional setting. We use this framework to analyze the role of wealth, health and education, in addition to income, as dimensions of multidimensional well-being in Germany. Our analysis shows that more than half of the German population is affluent in at least one dimension and less than 1% is affluent in all four dimensions. The likelihood of being rich in all dimensions is highest for prime-aged males from the West who live in couple households without children. Mobility between different affluence counts between 2002 and 2007 is rather low and existing changes are mostly driven by health and to a lesser extent by wealth.
Keywords: D31; D63; I0; I31; 330; Affluence; multidimensional measurement; mobility; elites; Vermögen; Einkommensverteilung; Vermögensverteilung; Gesundheit; Bildungsniveau; Elite; Soziale Mobilität; Deutschland